2016
DOI: 10.1080/15376516.2016.1236424
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of bone markers in rats induced nano-zinc oxide by qurecetin and α-lipolic acid

Abstract: The purpose of this study was to evaluate the potential protective effect of qurecetin (Qur) and α-lipolic acid (ALA) to modulate the perturbation of bone turnover which is induced by nano-zinc oxide (n-ZnO). Rats were fasted overnight and randomly divided into two groups: G1, normal healthy animals and the other rats were administered zinc oxide nanoparticles orally by guava in a dose of 600 mg/kg body weight/d for 5 sequential days in Wistar albino male rats. N-ZnO-exposed animals were randomly sub-divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Moreover, Many studies have documented that high doses of ZnO-NPs can cause apoptosis in liver and produce oxidative stress [23] and also they can induce liver DNA damage [24]. Moreover, a high dose of ZnO-NPs can induce bone resorption in rats [25]. In addition, Han et al [26] proved that ZnO-NPs may have an adverse effect on the rat's hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Many studies have documented that high doses of ZnO-NPs can cause apoptosis in liver and produce oxidative stress [23] and also they can induce liver DNA damage [24]. Moreover, a high dose of ZnO-NPs can induce bone resorption in rats [25]. In addition, Han et al [26] proved that ZnO-NPs may have an adverse effect on the rat's hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin reduced the levels of IL-1β, TNF-α and IL-6 while increasing those of IL-10 and Arg-1 in RAW264.7 cells exposed to M-CSF, RANKL or LPS [45,46,99]. In vivo, a reduction in TNF-α, IL-6 and CRP levels was observed following quercetin or quercetin-loaded phytosome nanoparticle interventions in ovariectomised [30] and zinc-oxide-nanoparticle-treated rats [44].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 87%
“…STZ-induced diabetic rats orally treated with quercetin for 8 weeks [39]. Along with the elevation of bone formation markers and reduction in bone resorption markers, Abdelkarem et al (2016) also found a decrease in NO• and DNA damage in rats exposed to zinc oxide nanoparticles and treated with quercetin [44]. Nonetheless, no effect was observed in oxidative-stress biomarkers and antioxidant activities when quercetin was orally supplemented to healthy rats [43].…”
Section: Antioxidative Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 126 studies were identified by the initial database search and 19 eligible studies [4,27,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] containing 21 comparisons were included in this study ultimately. The process followed for study selection is shown in Figure 2.…”
Section: Study Selectionmentioning
confidence: 99%